ISSUES OF TEACHING ENGLISH ACADEMIC WRITING IN MEDICAL HIGH SCHOOLS (Scientific journal of the Fergana State University, 2025)
Academic writing as one of the important components in the process of teaching English very often causes difficulties for students of medical universities, however, most of the subject material and vocabulary in the study of professional English refers specifically to written works such as annotations to the text, reviews of medical articles, essays and other works related to medical terminology. Due to the deficiency of research and informative analysis in Uzbek language on the academic writing in non-lingual high schools, it became necessary to study the preferences and effectiveness of scientific style of writing in professional English. The results of the study presented in this research show the effectiveness of using academic writing not only in the educational process but also in the further scientific activity of the student. When compiling methods for teaching academic writing in a medical school, the specifics of professional study of English were taken into account, which was proven by the example of experimental tests of the study. In the future, the issues and results of the study can be useful for teachers of English in medical schools in practice and become the subject of research on academic writing for scientific specialists.